Problem-Solving Ability and Self-Efficacy Based On Geometry Thinking Level In Van Hiele Learning - Widiyaningsih, Endang; Zaenuri, Zaenuri; Dwijanto, Dwijanto (Unnes Journal of Mathematics Education Research, 2020)
The objectives of this study are to test the effectiveness of van Hiele's learning of students; problem-solving ability and describe their problem-solving ability and self-efficacy based on the level of geometrical thinking. This research was a type of mixed quantitative and qualitative research. The study was conducted at MTs Asy-Syarifah in the 2015/2016 academic year. The research subjects were eighth grade students consisting of one experimental class with treatment using van Hiele learning and one control class. Hypothesis testing used a one-tailed proportion test and an average difference test. The results are obtained that van Hiele learning is effective in students' problem-solving ability. The average score of students who get van Hiele learning is higher than students who get expository learning. Students at level 2 (informal deduction) can reach all indicators of problem-solving. Students at level 2 can carry out the stages of problem-solving according to Polya's steps. Students at level 1 (Analysis), the students have not been able to carry out the completion plan appropriately. Students have difficulty in implementing a problem-solving plan. Students at level 0 (visualization) have not been able to plan properly. The results of the analysis of the three dimensions of students’ initial self-efficacy show that students: (1) still have difficulties and try to avoid difficult tasks, (2) give up easily when facing difficulties.